PERAN KEPUASAN KERJA SEBAGAI MEDIASI ANTARA ATRIBUT KEPEMIMPINAN DAN KOMITMEN ORGANISASI - Muhammad Rahyu Afani; Rafki Junaidi; Sefnedi Sefnedi; Zaitul Zaitul (JURNAL MANAJEMEN UNIVERSITAS BUNG HATTA, 2021)
Research on leadership attributes in influencing organizational commitment with job satisfaction as an intervening variable at PT. Mutiara Agam Palm oil processing with respondents of all employees totaling 39 people, with the result that the Leadership Attribute has a positive effect on Job Satisfaction and Job Satisfaction has no effect on Organizational Commitment, subsequently the Leadership Attribute has a positive effect on Organizational Commitment and Job Satisfaction does not mediate the relationship between Leadership Attributes and Organizational Commitment.